ULF wave power features in the topside ionosphere revealed by Swarm observations. Issue 17 (12th September 2015) - Balasis, Georgios; Papadimitriou, Constantinos; Daglis, Ioannis A.; Pilipenko, Viacheslav
Abstract Recently developed automated methods for deriving the characteristics of ultra low frequency (ULF) waves are applied to the Swarm data sets in order to retrieve new information about the near‐Earth electromagnetic environment. Here we present the first ULF wave observations by Swarm, analyzing 1 year data from the mission. We find evidence for the decay of the amplitude of the Pc3 (20–100 mHz) signal with altitude in the topside ionosphere as predicted by theoretical models of wave propagation. We show that the major characteristics of the Swarm ULF power maps generally agree with respect to the wave activity seen by the upper satellite and the lower pair of satellites when the power spectrum of the upper satellite is shifted by 1 h in magnetic local time. Moreover, a puzzling enhancement, not predicted by current ULF wave theories, of compressional Pc3 wave energy was revealed by Swarm in the region of South Atlantic Anomaly.